Nest-site selection of Hooded Crow (Corvus cornix) in urban environment - Kövér, László; Juhász, Lajos; Gyüre, Péter (Acta Agraria Debreceniensis, 2012)
In the past decade Hooded Crows showed a significant growth in Debrecen. The aim of this study was to become acquainted with Hooded Crows nest-site selection in urban circumstances. The research revealed that Hooded Crows are not choosy when it comes to selecting the species of the trees, but we noticed differences regarding nesting height - Hooded Crows living in the city build their nests in higher regions than those living in places outside Debrecen. We discovered a significant difference between nesting heights and the tree species, which is probably due to the different characteristics shown by the given tree species. As for nesting heights, we found that in typical urban habitats there were no relevant differences shown. Samet the situation, when we compared these habitats in pairs, it came to light that nesting heights - when comparing lonely trees - wood segments and tree raws – wood segments - did not show significant differences too, which can be explained by the various conditions provided by the habitats mentioned. To sum up, during our research the following results emerged: 1. Hooded Crows prefer approximately the same nesting heights in all kinds of habitats, urban environment and tree species. 2. Nesting height depends on the tree species but independent from habitat.